Mechanical properties of welded ultrahigh-strength S960 steel at low and elevated temperatures. (November 2022) - Keränen, Lassi; Nousiainen, Olli; Javaheri, Vahid; Kaijalainen, Antti; Pokka, Aki-Petteri; Keskitalo, Markku; Niskanen, Juhani; Kurvinen, Emil
Abstract: New ultrahigh-strength steels have been developed to meet the need for better performance, load bearing capacity, safety and weight saving. However, the design guidelines are incomplete, especially regarding the design of welded ultrahigh-strength steel components in fluctuating operating conditions. This reduces usability and can cause serious safety risks when the welded structures are in use. The heat input and cooling rate have a significant effect on the microstructure and mechanical properties of the ultrahigh-strength steels. Therefore, a model to predict the strength and microstructure, based on welding parameters, is required for designers to create safer solutions in engineering design. In this study, a 6 mm thick S960 low alloy ultrahigh-strength steel was welded using gas metal arc welding (MAG) and laser welding. The effects of welding heat input and operating temperature on the tensile properties, hardness, microstructure, and fracture mechanism of the welded specimens were investigated. The effects of operating temperature on the mechanical properties of welded joints were investigated by performing tensile tests between temperatures of −80 °C and + 400 °C. The unwelded base material was also tested in the same temperature range. The results showed a ductile fracture mechanism in all the samples regardless of the test temperature and welding heat input. However, the tensile strengths and elongations increased when the test temperature drops to −80 °C from room temperature. In addition, mathematical predictions for the strength and elongation properties, and grain sizes in heat-affected zones, as a function of temperature and welding heat input were proposed.